Advances in Multimedia Information Processing - PCM 2005 6th Pacific Rim Conference on Multimedia, Jeju Island, Korea, November 11-13, 2005, Proceedings, Part I - Ho, Yo-Sung; Kim, Hyoung Joong (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2005)
We are delighted to welcome readers to the proceedings of the 6th Pacific-Rim Conference on Multimedia (PCM). The first PCM was held in Sydney, Australia, in 2000. Since then, it has been hosted successfully by Beijing, China, in 2001, Hsinchu, Taiwan, in 2002, Singapore in 2003, and Tokyo, Japan, in 2004, and finally Jeju, one of the most beautiful and fantastic islands in Korea. This year, we accepted 181 papers out of 570 submissions including regular and special session papers. The acceptance rate of 32% indicates our commitment to ensuring a very high-quality conference. This would not be possible without the full support of the excellent Technical Committee and anonymous reviewers that provided timely and insightful reviews. We would therefore like to thank the Program Committee and all reviewers. The program of this year reflects the current interests of the PCM's. The accepted papers cover a range of topics, including, all aspects of multimedia, both technical and artistic perspectives and both theoretical and practical issues. The PCM 2005 program covers tutorial sessions and plenary lectures as well as regular presentations in three tracks of oral sessions and a poster session in a single track. We have tried to expand the scope of PCM to the artistic papers which need not to be strictly technical.